Planning to Reconfigure the 150 kV Transmission Network at PT. PLN (Persero) Tualang Cut Network and Substation - Hasibuan, Arnawan; Asran, Asran; Adriansyah, Fery; Ismail, Baharuddin; Siregar, Widyana Verawaty; Sayuti, Muhammad (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
System condition at PT. PLN (Persero) Tualang Cut Substation where the reliability of the 150 kV system depends on the Langsa Substation, which we will reconfigure on the Lgs-P.B and Lgs-T.C channels to P.B-T. C and T.C-Lgs. The planning for the reconfiguration of the 150 kv transmission network of the Tualang Cut Substation was carried out by estimating the distance of the transmission line and the constraints that occurred. The condition of the electric power system that is currently operating at PT. PLN (Persero) Tualang Cut Substation is considered less efficient in receiving power from the 150 kV SUTT interconnection. The SUTT in Tualang Cut currently receives electrical power from the Langsa Substation with a Losses value on lines 1 and 2 of 771,4142474 kW and experiences a Voltage Drop on lines 1 and 2 of 4,38 kV. After we reconfigured the channel, from the results of the reconfiguration there was a decrease in Losses on channels 1 and 2 by 311,298581 kW which before the reconfiguration of power losses on the line amounted to 771,4142474 kW and after being reconfigured to 460,1156668 kW there was a decrease in Voltage Drop on channels 1 and 2 by 1,44 kV, before the reconfiguration of the voltage drop on the line of 4,38 kV and after the reconfiguration to 2,94 kV, the reconfiguration carried out is the best solution to reduce losses and voltage drops.